0

How do i find the second derivative of e^{sinx} using product rule

**Comments**

cos(x)e^sin(x) (cos(x) - tanx)

0

y = e^{sinx}

dy/dx = cosx.e^{sinx}

To find the second derivative, we apply product rule,

V(du/dx) + U(dv/dx)

U = cosx

du/dx = -sinx

V = e^{sinx}

dv/dx = cosx.e^{sinx}

d^{2}y/dx^{2 }= e^{sinx}(-sinx) + cosx(cosx.e^{sinx})

d^{2}y/dx^{2} = cosx(cosx.e^{sinx}) - (sinx.e^{sinx})

d^{2}y/dx^{2} = e^{sinx}(cos^{2}x - sinx)

OR

d^{2}y/dx^{2} = cosx.e^{sinx}(cosx - tanx)

Your Answer